PRODUKTIVITAS TENAGA KERJA INDUSTRI PENGOLAHAN TEMBAKAU PADA PT INDONESIAN TOBACCO TBK. KOTA MALANG - Irma Rahman; Wahyu Hidayat; M. Sri Wahyudi (Jurnal Ilmu Ekonomi JIE, 2020)
Small and medium industries are industries that have the greatest potential anywhere, one of which is the tobacco processing industry in Malang. This industry has many positive impacts on society. This is because it can provide a large influence on the region, such as building job availability and can improve the local economy of the community itself. The purpose of this study was to analyze the level of productivity of the tobacco processing industry workforce at PT Indonesian Tobacco Tbk. Malang City, analyzed the level of education, wages, and age of labor productivity of the tobacco processing industry at PT Indonesian Tobacco Tbk. Malang city. This study uses primary data with questionnaire data collection methods. The analytical tool used is multiple linear regression with cross-section data models. The results showed that the coefficient of determination obtained by 0.982, which means that 98.2 percent of changes in labor productivity is influenced by variables of education level, wages, and age, while 1.8 percent is caused by other factors not included in the regression equation.